Links Between Peer Victimization, Perceived School Safety, and Internalizing Symptoms in Middle Childhood. Issue 4 (1st December 2019) - Fite, Paula J.; Poquiz, Jonathan; Díaz, Kathleen I.; Williford, Anne; Tampke, Elizabeth C.
Abstract: Extant research indicates that peer victimization is an important factor in the development of internalizing symptoms for youth. However, few studies have examined contextual factors that may impact how peer victimization contributes to these symptoms in middle childhood, especially in the form of victimization. The current study evaluated associations between relational and physical victimization and symptoms of depression and anxiety in a sample of third through fifth graders. In addition, the influence of perceived school safety as a moderator of these associations was examined. Findings indicated that relational victimization was more strongly associated with symptoms of both depression and anxiety than physical victimization. Further, low levels of perceived school safety contributed to symptoms of depression and anxiety and exacerbated the associations between relational victimization and these symptoms, particularly for anxiety. Implications for findings are discussed.